2010
DOI: 10.1080/00131881.2010.504060
|View full text |Cite
|
Sign up to set email alerts
|

Self-rating and respondent anonymity

Abstract: Background: Most empirical investigations in survey research have been conducted using self-reported or self-evaluated item responses. Such measures are common because they are relatively easy to obtain and are often the only feasible way to assess constructs of interest. In order to improve on the validity of self-reports it has become a common practice to disguise the identities of respondents or to assure them of the confidentiality of their responses. Purpose: The purpose of this study is to investigate th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
1
1
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 29 publications
0
2
0
Order By: Relevance
“…Other research has shown the lack of accountability associated with complete anonymity potentially jeopardizes the validity of survey responses by fostering satisficing [26]. However, there is also evidence that topical clarity and cultural influences can effectively reduce the difference between anonymous and non-anonymous responses to insignificance [17].…”
Section: Instrumentmentioning
confidence: 99%
“…Other research has shown the lack of accountability associated with complete anonymity potentially jeopardizes the validity of survey responses by fostering satisficing [26]. However, there is also evidence that topical clarity and cultural influences can effectively reduce the difference between anonymous and non-anonymous responses to insignificance [17].…”
Section: Instrumentmentioning
confidence: 99%
“…However, there have been just as many studies that could not prove that there are any differences between anonymous and personalised data [7], [8]. Furthermore, the teaching staff adopts an attitude, in accordance with the basic educational concept, that students should be treated as adult partners and that an objective and open exchange regarding the performance quality must be possible.…”
Section: Introductionmentioning
confidence: 99%